2018
DOI: 10.3906/sag-1706-141
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio and microvascular complications in subjects with type 2 diabetes: Pakistan’s perspective

Abstract: Background/aim: The aim of this study is to find the association between diabetic microvascular complications and the neutrophil-to-lymphocyte ratio (NLR) in subjects with type 2 diabetes. Materials and methods: This was a retrospective study based on hospital data records from January 2005 to May 2016 at the Baqai Institute of Diabetology and Endocrinology. The eligibility criteria included subjects with type 2 diabetes with their latest complete blood count while subjects with conditions such as chronic infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 18 publications
4
13
2
Order By: Relevance
“…Our findings were contrasting to the finding of Fawad et al, in which a significant correlation was observed between NLR and HbA1c whereas no such correlation was observed in our study [18]. Poor glycemic control is indicated by HbA1c levels and thus increased HbA1c levels may correlate withincreased risk of complications but no such correlation was observed in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings were contrasting to the finding of Fawad et al, in which a significant correlation was observed between NLR and HbA1c whereas no such correlation was observed in our study [18]. Poor glycemic control is indicated by HbA1c levels and thus increased HbA1c levels may correlate withincreased risk of complications but no such correlation was observed in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study demonstrated that NLR were significantly higher in patients with diabetic neuropathy and patients with longer duration of diabetes (p<0.05) and also mean NLR was significantly higher in patients with diabetic neuropathy (p<0.05).The findings of preset study were supported by findings of Chittawar et al, where number of microvascular complications were significantly higher in patients with a longer duration of diabetes and raised [17]. Fawad et al, also reported findings similar to our study [18]. The findings of our study were also supported by an Egyptian study by Moursy et al, in which significant increase was found in NLR between diabetic subjects with and without neuropathy [19].…”
Section: Discussionsupporting
confidence: 91%
“…HbA1c was measured by HPLC method on a Bio-Rad D-10. 10 Height was measured to the nearest of 0.1cm, while individual standing in erect posture and weight was measured with portable weighing scale nearest of 0.1 kilogram (kg). Body Mass Index (BMI) was measured as the ratio of weight (kg) to height squared (m 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…24 A Japanese study showed that NLR might be a potential factor for evaluating diabetic patients with a higher degree of albuminuria, 25 suggesting that NLR may predict the existence of microvascular complications. 26 In diabetic patients, abnormal insulin action may lead to increased platelet adhesion.…”
Section: Dovepress 2053mentioning
confidence: 99%